Jimmy Carter's economy : policy in an age of limits - Biven, W. Carl. (Chapel Hill : University of North Carolina Press, 2002)
"In Jimmy Carter's Economy, Carl Biven traces how the Carter administration developed and implemented economic policy amid multiple crises and explores how a combination of factors beyond the administration's control came to dictate a new paradigm of Democratic Party politics." "Based on an examination of original documents and on interviews with many of Carter's principal advisers, Jimmy Carter's Economy is a case study of the challenges facing presidential economic policymakers. Written for historians and political scientists as well as economists, the book is also accessible to general readers with an interest in the transformation of the American political and economic landscape."--BOOK JACKET.
Ch. 1. How It Ended: The 1980 Campaign -- Ch. 2. How It Began: The 1976 Campaign -- Ch. 3. The New Administration: The Process of Economic Advice -- Ch. 4. The Stimulus Package -- Ch. 5. The Mondale Mission and the London Summit -- Ch. 6. Strategy for Inflation -- Ch. 7. The Bonn Summit -- Ch. 8. Bonn and Oil: The Internal Debate -- Ch. 9. The Worsening Inflation -- Ch. 10. Government Actions and Inflation -- Ch. 11. Enter Paul Volcker -- Ch. 12. Jimmy Carter and the Age of Limits.
Includes bibliographical references (p.321-338) and index.
Keywords: Carter, Jimmy, -- 1924-; United States -- Economic policy -- 1977-1981.; United States -- Economic conditions -- 1977-1981.; United States -- Politics and government -- 1977-1981.